Seventh Grade Math Help?

1) -3s+2(-5s+1) if s = -3

2) -1+9(4d-2)-6d if d = -1

3) 6-2y-6(-3y+7) if y = 3

4) -8(9+2k)+8k+K if K = 6

5) -w-5+5(-5w+9) if w = 1

4 Answers

Relevance
  • 7 years ago
    Best Answer

    Hi there --

    Two things to keep in mind with these problems -- first, just make sure you follow your order of operations once you substitute; and second, make sure you substitute accurate, watching for transpositions between s and 5, and l and 1, and capitals and lowercase (since they can possibly mean different things when the capital form of the letter stands for one quantity and the lowercase form of the letter stands for another quantity). With that in mind:

    1) -3s + 2(-5s + 1); s = -3

    . . . . -3(-3) +2(-5∙-3 + 1)

    . . . . 9 + 2(15 + 1)

    . . . . 9 + 2(16)

    . . . . 9 + 32

    . . . . 41

    2) -1 + 9(4d - 2) - 6d; d = -1

    . . . . -1 + 9(4∙-1 - 2) - 6∙-1

    . . . . -1 + 9(-4 - 2) - (-6)

    . . . . -1 + 9(-6) + 6

    . . . . -1 + -54 + 6

    . . . . -55 + 6

    . . . . -49

    3) 6 - 2y - 6(-3y+7); y = 3

    6 - 2∙3 - 6(-3∙3 + 7)

    . . . . = 6 - 6 - 6(-9 + 7)

    . . . . = 6 - 6 - 6(-2)

    . . . . = 6 - 6 - (-12)

    . . . . = 0 + 12

    . . . . = 12

    4) -8(9 + 2k) + 8k + k; k = 6

    -8(9 + 2∙6) + 8∙6 + 6

    . . . . = -8(9 + 12) + 48 + 6

    . . . . = -8(21) + 48 + 6

    . . . . = -168 + 48 + 6

    . . . . = -120 + 6

    . . . . = -114

    5) -w - 5 + 5(-5w + 9); w = 1

    -1 - 5 + 5(-5∙1 + 9)

    . . . . = -1 - 5 + 5(-5 + 9)

    . . . . = -1 - 5 + 5(4)

    . . . . = -1 - 5 + 20

    . . . . = -6 + 20

    . . . . = 14

    I put together a short video tutorial which further illustrates these solutions, and referenced it as a source below. We hope it is helpful.

  • 7 years ago

    -3s + 2(-5s+1)

    -3s + (-10s) + 2

    -13s + 2

    -13(-3) + 2

    39 + 2

    41

    -1 + 9(4d-2) - 6d

    -1 + 36d - 18 - 6d

    30d - 19

    30(-1) - 19

    -30 - 19

    -49

    6 - 2y - 6(-3y + 7)

    6 - 2y - (-18y + 42)

    6 - 2y + -1(-18y + 42)

    6 - 2y + 18y - 42

    16y - 36

    16(3) - 36

    48 - 36

    12

    -8(9 + 2k) + 8k + k

    -8(2k + 9) + 9k

    -16k - 72 + 9k

    -7k - 72

    -7(6) - 72

    -42 - 72

    -114

    -w - 5 + 5(-5w + 9)

    -w - 5 + (-25w) + 45

    -26w + 40

    -26(1) + 40

    -26 + 40

    14

  • Sde
    Lv 4
    7 years ago

    Just put the number into the expression: for example

    1)

    -3 (-3) + 2 [-5 (-3) + 1] = +9 + 2 (15 + 1) = 9 + 2*16 = 9 + 32 = 41.

    So you just need to do the math:)

  • 7 years ago

    1)41

    2)-61

    3)61

    4)iidk sorry

    5)10

Still have questions? Get your answers by asking now.